Water absorption and low-energy impact and their role in the failure of ±45° carbon fibre composites - Feras Korkees (Polymer Composites, 2018)
Defects in polymer composites associated with in-service damage induced by impact and those produced by environmental degradation due moisture absorption can have a significant influence on the mechanical properties and failure modes of the structures. This study evaluates the flexural characteristics and failure modes of ±45° carbon/epoxy laminates under different conditions. The flexural strength and stiffness of these composites were inspected before and after subjecting to water absorption, drying, re-drying and low energy impact. It was observed that both absorbed water and low energy impact caused significant deformations and fractures which drastically reduced the load carrying ability of the ±45° carbon/epoxy laminates. Re-drying slightly improved the properties and reversed the effects of water.